Hubungan Fluktuasi Parameter Fisika dalam Produksi Garam Rich Minerals Dengan Media Prototype di Salt House - Yoseva, Vellia; Indriyawati, Novi; Pratiwi, Wiwit Sri Werdi; Efendy, Makhfud (Universitas Trunojoyo Madura, 2021)
Madura Island is one of the largest salt producing areas in Indonesia. Salt is included in the type of complementary ingredients in every dish. Rich Mineral salt is salt obtained from the total crystallization process without removing various minerals contained in the raw materials, so that the mineral content is higher than consumption salt in general. This study aims to describe the fluctuations and the relationship between physical parameters consisting of water temperature, water density and water level during the salt production process. This study uses three prototype geomembranes with a size of 60x40x16 cm in salt production. This study uses quantitative methods in the form of numbers obtained based on facts in the field. The results of this study are that the three prototypes have a temperature range, water density and water level that are not significantly different. This is showed by the results of the ANOVA test, where the P-value of the three prototypes is greater than the alpha value (α). In this study also obtained a correlation value between the parameters of water density and water level. The correlation value resulting from the calculation of the linear equation between the two parameters is 0.93. Based on these results, it can be interpreted that the water density and water level have a correlation relationship of 93%. So, it can be concluded that the higher the water level, the lower the water level.